Compliance of Public Fuel Filling Stations (SPBU) with Fuel Pump Accuracy in Consumer Protection Efforts - Akbar, Soultan Raffly; Sakti, Muthia (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The accuracy of fuel pumps at public fuel filling stations (SPBU) is an essential factor in ensuring fair transactions and consumer protection. This study aims to analyze the level of compliance of SPBUs with fuel pump accuracy standards and examine the role of the Ministry of Trade in monitoring potential measurement discrepancies. The research method used is a normative juridical approach supported by empirical data from several cases of measurement manipulation, such as the installation of printed circuit boards (PCBs) in Sukabumi, measurement reduction in Serdang Bedagai, and the use of remote control devices in Bogor. The study’s results show that gas station compliance remains partial. Formally, some gas stations have carried out calibration and recalibration. However, substantively, there are still practices of manipulation that violate Law Number 2 of 1981 concerning Legal Metrology and Law Number 8 of 1999 concerning Consumer Protection. The Ministry of Trade conducts supervision through calibration/recalibration, field inspections, and the enforcement of sanctions, supported by internal oversight from Pertamina, a state-owned enterprise. However, the effectiveness of supervision is still hampered by limited resources, the development of technical manipulation methods, and low legal awareness among business actors. This study emphasizes the need for intensive, multi-layered supervision, the digitization of metrology, and strict law enforcement to ensure accurate fuel measurements and optimal consumer protection.